Prevalence of suspected poor bone health in people with chronic obstructive pulmonary disease – a cross-sectional exploratory study. (12th August 2022) - Cecins, Erin; Cavalheri, Vinicius; Taaffe, Dennis R; Hill, Anne-Marie; Hug, Sarah; Hill, Kylie
Background: Compared to the general population, adults with chronic obstructive pulmonary disease (COPD) have an increased prevalence of osteoporosis. Despite the known risk factors and potential complications of compromised bone health in COPD, little is known about whether poor bone health is routinely suspected. We measured, in people with COPD, the prevalence of those who had one or more indicators suggestive of suspected poor bone health, and compared the characteristics of those with versus without these indicators. Methods: Data were collected from adults with COPD presenting to three tertiary hospitals. Indicators of suspected poor bone health were defined as any of the following criteria: (i) self-reported problems with bone health, (ii) previous imaging for bone health, (iii) history of fragility fracture or, (iv) advised to use medication/supplements to optimise bone health. Characteristics compared between those with versus without indicators of suspected poor bone health comprised age, sex, body mass index (BMI), FEV1 % predicted and recruitment setting. Results: 361 participants were included (age 70 ± 10, BMI 27.9 ± 7.8 kg/m 2, FEV1 % predicted 49 ± 20; 161 [45%] female). Indicators suggestive of suspected poor bone health were present in 53% (95% confidence interval [CI] 47–58) of the participants. The odds of this outcome increased with advancing age (odds ratio; OR [95% CI] 1.05 [1.03 to 1.08]) and being female (OR [95% CI] 3.4 [2.2 to 5.7]) . Conclusion: In people with COPD, the odds of having indicators suggestive of suspected poor bone health increase with advancing age and in females. Further work is required to promote the importance of bone health in this population.